Use of three inoculation methods in screening cowpea genotypes for resistance to two Colletotrichum species - Adebitan, S.A.; Ikotun, T.; Dashiell, Kenton E.; Singh, S.R. (1992)
Twelve cowpea cultivars were screened for reactions to infection by Colletotrichum lindemuthianum and C. truncatum, causal agents of anthracnose and brown blotch diseases, respectively. Three different inoculation techniques were used: spraying a spore suspension on leaves of seedlings, injecting a spore suspension into stems, and wrapping wounded seedlings with inoculum meal of Colletotrichum spp was the best method of inoculation because it produced optimal conditions for infection and disease development.